2005
DOI: 10.1002/hup.674
|View full text |Cite
|
Sign up to set email alerts
|

Is cannabis an anti-antipsychotic? The experience in psychiatric intensive care

Abstract: Our findings suggest that cannabis abusers had a more severe psychotic illness, especially in schizophrenia. There are additional complications in terms of weight gain for cannabis users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In the UK, it is estimated that between 20 and 70% of people with severe mental illness use cannabis (Miles et al, 2003;Isaac et al, 2005). A review of 53 treatment samples and 5 epidemiological studies examining the prevalence of cannabis use and misuse among people with psychosis reported lifetime use in 42% and lifetime misuse in 22.5% (Green et al, 2005).…”
Section: Atakanmentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, it is estimated that between 20 and 70% of people with severe mental illness use cannabis (Miles et al, 2003;Isaac et al, 2005). A review of 53 treatment samples and 5 epidemiological studies examining the prevalence of cannabis use and misuse among people with psychosis reported lifetime use in 42% and lifetime misuse in 22.5% (Green et al, 2005).…”
Section: Atakanmentioning
confidence: 99%
“…Prevalence of current use was reported to be 23% and current misuse 11.3%. A UK study involving 115 patients in a psychiatric intensive care unit found that 71.3% were mis using cannabis (Isaac et al, 2005). These individuals were found to be more severely ill and spent longer periods in hospital care than those who did not use the drug.…”
Section: Atakanmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenic patients with a history of marijuana abuse are generally younger when they are first admitted to hospitals and tend to have more admissions to hospitals than schizophrenic patients who are not marijuana users (Isaac et al 2005). Poorer prognosis, higher reality distortion and more positive symptomatology are also characteristic of substance-using patients with schizophrenia (Baker et al 2005;Hambrecht and Hafner 2000).…”
Section: Amphetamine/methamphetaminementioning
confidence: 97%
“…They were also innovative in that they addressed a range of needs, including substance use which further increases physical morbidity in people with severe mental illness. 18,19 Resources Resources are important. The Hamilton team was lucky to have a community dietician and a mental health-specific smoking cessation specialist.…”
Section: Lifestyle Changesmentioning
confidence: 99%